The Implementation Of Community-Based Total Sanitation At Puskesmas Pasundan Garut Regency And Its Law Enforcement Is Connected With The Fulfillment Of The Right To A Good And Healthy Environment - Rahayu, Meisya Dewi (Fakultas Hukum, Universitas Islam Bandung, 2023)
Until moment this implementation Community Based Total Sanitation (STBM) in the district Garut still weak , so impact to environment life very take effect big . Public health center In implementation STBM implementation in Puskesmas Pasundan through trigger not yet in accordance as mandated by the regulation of the Minister of Health Number 3 of 2014 concerning Community Based Total Sanitation. Problem in thesis is How Implementation Community Based Total Sanitation based on Minister of Health Regulation Number 3 of 2014 concerning Community Based Total Sanitation at UPT Puskesmas Pasundan Regency Garut and how enforcement law to implementation Community Based Total Sanitation based on Minister of Health Regulation Number 3 of 2014 concerning Community Based Total Sanitation at UPT Puskesmas Pasundan connected with fulfillment right on good and healthy environment.